Electroencephalographic and cognitive task analysis of working memory and attention in athletes: A systematic review. - Delgado, Pedro; Passos, Pedro; Tavares, Francisco; Ferreira, Hugo Alexandre (Psychology of Sport & Exercise, 2025)
This study aimed to systematically review the current research on the cognitive ability of athletes, specifically, in working memory, attention, problem-solving and decision-making tasks. The objective was to examine the differences in cognitive abilities between athletes and non-athletes, and between athletes from different sports. To this end, a search was conducted on PubMed and Scopus for original articles published before November 28th, 2023, that used electroencephalography (EEG) in sports or with athletes engaged in at least moderate-intensity activities, evaluated healthy adults or children through case-control studies, and analyzed at least one of four cognitive tasks (working memory, attention, problem-solving and decision-making). The risk of bias and quality assessment was performed using the Newcastle-Ottawa Scale. The following results were extracted from the included studies: population; publishing year; type of sport; type of controls (athletes or general population); cognitive task results; brain wave frequencies analyzed; and brain wave components analyzed. Following the review of 697 studies, 35 met the inclusion criteria. Most studies reported that athletes outperformed controls in cognitive tasks, both in terms of accuracy and reaction time. Individual sports showed better performances, and martial arts and boxing showed good reaction times but poor accuracies. Increased cortical activity was also observed in athletes when compared with controls. Despite some limitations – primarily the number of studies performing sport-specific tasks or comparing the athletes with less experienced counterparts - results indicate a clear over-performance in cognitive tasks by athletes compared to controls, as well as definitive cognitive differences between different sports. • Athletes demonstrate enhanced cognitive performance and higher cortical activation. • Different sport expertise leads to distinct cognitive and cortical activity. • Individual sports athletes outperformed team sports athletes. • Wave component analysis is the most effective in measuring athletes' cognition.